ANALISIS PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN HONDA REVO FIT FI (Studi pada Astra Motor Ngaliyan Jl. Prof. Ddr. Hamka Blok 1 No. 122, Semarang) - Dinata, Alayka Hardandy; Tri Astuti, Sri Rahayu (Faculty of Economics and Business Diponegoro University, 2015)
This research aims to test the effect of product quality, price perception and promotions on the purchasing decision on Astra Motor Ngaliyan. Drop in sales experienced by the Astra Motor Ngaliyan background problem in this research.In this research using a method of collecting data with a questionnaire with the number of samples 75 respondents, the sample accidental use sampling techniques and methods of analysis of data used in this research is linear regression worship of idols.The result of this research shows that all the independent variable that is a product quality,price perception and promotion has links positive in line against the dependent variable for which is purchasing decisions. The testing of hypotheses using test t show that the three independent variable for which researched proved to be significantly affect the decision purchase. Then through the f can be known that in the three joint of a variable that affected decision purchase. Figures adjusted r square worth 0,528 show that the independent variable can explain 52,8% decision the purchase of the remaining 47,2% by other variables out of one variable are used in this research